Edukasi Gizi dan Praktik Pengolahan Pemberian Makanan Tambahan Pangan Lokal untuk Balita - Indah Purnama Sari; Windi Indah Fajar Ningsih; Ditia Fitri Arinda; Haerawati Idris (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
Toddlers are a population group vulnerable to nutritional and health problems. The prevalence of wasting among toddlers in Ogan Ilir Regency remains relatively high. One strategy to support improvements in children's nutritional status is the utilization of local food resources as healthy snacks. This community service program was conducted in Ibul Besar I Village from June to October 2025. Preliminary observations revealed that local foods had not been utilized as snacks for toddlers, while the consumption of unhealthy snacks was relatively high due to their easy accessibility within the village. In addition, mothers of toddler had never received nutrition education or practical training on the preparation of snacks based on local food resources. This program aimed to improve the knowledge and skills of mothers of toddler through nutrition education and hands-on training in the preparation of puanchi bar, an innovative nutritious snack made from snakehead fish flour and developed as an alternative supplementary food for young children. The product contains essential nutrients that support child growth and development. A total of 24 mothers participated in activities consisting of educational sessions, demonstrations, and practical training. Program evaluation was conducted through pre- and post-intervention knowledge assessments using a questionnaire, as well as observation of participants’ skills during the practical sessions. The results showed a significant improvement in mothers’ knowledge regarding healthy snacks and the utilization of local food resources (p0.001). In addition, all participants were able to prepare puanchi bar independently and actively engaged throughout the program. The intervention not only enhanced participants’ knowledge but also strengthened their skills in utilizing local food resources to prepare nutritious snacks for toddlers.